Identification of miRNA from Bouteloua gracilis, a drought tolerant grass, by deep sequencing and their in silico analysis. (February 2017) - Ordóñez-Baquera, Perla Lucía; González-Rodríguez, Everardo; Aguado-Santacruz, Gerardo Armando; Rascón-Cruz, Quintín; Conesa, Ana; Moreno-Brito, Verónica; Echavarria, Raquel; Dominguez-Viveros, Joel
Graphical abstract: Highlights: We identified 31 conserved miRNAs families and 53 putative novel miRNAs in B. gracilis . Two putative miRNA sequences were unique to B. gracilis and they had B. gracilis -specific ESTs as targets. Predicted miRNAs putatively regulate mRNA genes that are involved in biological processes such as metabolism, plant growth and development, and stress responses. Abstract: Background: MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate signal transduction, development, metabolism, and stress responses in plants through post-transcriptional degradation and/or translational repression of target mRNAs. Several studies have addressed the role of miRNAs in model plant species, but miRNA expression and function in economically important forage crops, such as Bouteloua gracilis ( Poaceae ), a high-quality and drought-resistant grass distributed in semiarid regions of the United States and northern Mexico remain unknown. Results: We applied high-throughput sequencing technology and bioinformatics analysis and identified 31 conserved miRNA families and 53 novel putative miRNAs with different abundance of reads in chlorophyllic cell cultures derived from B. gracilis . Some conserved miRNA families were highly abundant and possessed predicted targets involved in metabolism, plant growth and development, and stress responses. We also predicted additional identified novel miRNAs with specific targets, including B. gracilis ESTs, which were detected under drought stress conditions. Conclusions: Here we report 31 conserved miRNA families and 53 putative novel miRNAs in B. gracilis . Our results suggested the presence of regulatory miRNAs involved in modulating physiological and stress responses in this grass species.